Noninvasive assessment of the presence and size of esophageal varices - Petrović, Gordana; Nagorni, Aleksandar; Bjelaković, Goran; Benedeto Stojanov, Daniela; Radovanović Dinić, Biljana (Vojnosanitetski pregled, 2023)
Background/Aim. A significant number of patients with liver cirrhosis who underwent screening endoscopy do not have esophageal varices (EVs) or have EVs that do not require prophylactic therapy. Given the invasiveness of the procedure, the need to develop nonendoscopic methods in predicting the presence of EVs is reasonable. The aim of the study was to determine the significance of clinical, biochemical, and ultrasonic parameters in the prediction of EVs. Methods. The study included 59 patients with cirrhosis of the liver, 39 (66.1%) patients with EVs, and 20 (33.9%) patients without EVs. In the group of patients with EVs, 22 (56.4%) patients had small EVs, and 17 (46.3%) had large EVs. Clinical parameters that included Child-Pugh (CP) score, ascites, and splenomegaly were evaluated. In all participants, complete blood count, liver function tests, abdominal ultrasound, and gastroscopy were performed, and a platelet count/spleen diameter (PC/SD) ratio was calculated. Results. Univariate logistic regression analysis showed that independent risk factors for the occurrence of EVs were the following: CP B class [odds ratio (OR) 6.67; p = 0.003] and CP C class (OR 23.33; p = 0.005) relative to class A, ascites (OR 7.78; p = 0.001), spleen size (OR 1.035; p = 0.016), bilirubin (OR 1.065; p = 0.007), albumin (OR 0.794; p = 0.001), prothrombin time (OR 0.912; p < 0.001), international normalized ratio-INR (OR 231.364; p < 0.001), platelet count (OR 0.989; p = 0.023), and PC/SD ratio (OR 0.999; p = 0.034). In a multivariate model, it was shown that a decreased platelet count was a statistically significant risk factor for the presence of EVs (OR 0.983; p = 0.023). Leukopenia and the size of the right liver lobe were found to be statistically significant factors for the occurrence of large EVs. Based on the receiver operating characteristic (ROC) curve for the PC/SD ratio, the cutoff value of the test was obtained at 907 (907.11), with a negative predictive value of 76.4% for large EVs. Conclusion. The cutoff value of PC/SD ratio < 907 has a predictive value for the occurrence of large EVs.